Raising self-consciousness: phonetic education as embodied language learning - Scivoletto, Giulio (Glottodidactica, 2022)
Phonetic education is presented in this contribution as a pedagogical approach and didactic method for teaching and acquiring phonetic-phonological competence in the foreign language classroom at school. To develop such competence, we should overcome the school practice that still today does not seem to deviate from the listen-and-repeat method: the teaching of articulatory phonetics is proposed as a method and tool for learning based on self-consciousness. By discovering the sound dimension of language, and the bodily reality through which it is realised, the student undergoes an educational experience based on perception. The formative value of a phonetic education is framed in the perspective of body pedagogy, in line with an inclusive and democratic approach to language education.